Pouso Alegre (MG): expansão urbana e as dinâmicas socioespaciais em uma cidade média - Andrade, Alexandre Carvalho de [UNESP] (2013)
Because of its importance in the current Brazilian urban network, the medium-sized cities are being increasingly analyzed, the more distinct motivations. In this research, the city of Pouso Alegre is analyzed by means of the interaction between temporal and spatial scales, which allows us to highlight its historical urbanization process, its role in regional urban network and the dynamics of their intraurbano space. In the previous period the construction of Fernão Dias highway, Pouso Alegre was in a situation of economic and demographic stagnation, which was reversed from the sixties of the twentieth century, by factors such as the improvement of road transport systems and attracting businesses, that favored economic diversification, population growth and greater representation of the city in regional urban network. Because of these processes, new socio-spatial dynamics began to focus on the urban space of Pouso Alegre, serves as examples of the new centralitys